Evaluation of C-reactive Protein-Albumin-Lymphocyte (CALLY) Index in the Pathogenesis of Osteoporosis - Karakeci, Emel Sabaz; Aydogdu, Nesibe (Galenos Publ House, 2026)
Objective: To assess the relationship between bone mineral density (BMD) and the C-reactive protein-albumin-lymphocyte (CALLY) index in postmenopausal women. Materials and Methods: A cross-sectional analysis of 337 postmenopausal women [107 with osteoporosis (OP), 144 with osteopenia, and 86 controls] was conducted from January 2023 to December 2024. Participants were stratified by BMD using DXA T-scores: normal >=-1, osteopenia -1 to -2.5, OP <=-2.5. Hematological parameters (C-reactive protein, albumin, lymphocyte counts) were analyzed, and the CALLY index was derived. Results: No statistically significant difference in CALLY index scores was observed between groups (p = 0.130). However, albumin and lymphocyte levels were significantly lower in the OP group than in the normal group (p = 0.002). Conclusion: Low albumin and lymphocyte levels observed in the OP group underscore the significance of these parameters in the pathogenesis of bone loss. However, the CALLY index, which integrates these parameters, does not offer sufficient discrimination for assessing the low-grade systemic inflammation associated with OP. Prospective studies with larger sample sizes may help clarify the role of the CALLY index in the etiology of OP.
Keywords: Bone mineral density; CALLY index; hematological index; inflammation; osteoporosis